EFFECT OF STRATEGIC LEADERSHIP STYLE AND GREEN HUMAN RESOURCE MANAGEMENT ON THE MANAGEMENT PERFORMANCE OF KODAM JAYA - abdurachman, dudung; Arafah, Willy; Kusnad (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this research is to pay attention to environmental developments and dynamic strategic contexts that affect the implementation of national defense. Especially in facing challenges in national defense. In the current Reformation Era, the Commander of the Military Region of Kodam Jaya has many tasks to prevent problems in society, especially in the current pandemic era. The Jaya Regional Military Command is able to maintain stability, establish cooperation with various parties, coordinate to maintain order by disbanding crowds that will bring danger and safety to the state, especially the people of Jakarta. The research design and method used in this research is hypothesis testing. This research is a quantitative non-experimental, using a questionnaire given to 93 respondents. This research was carried out at the Jaya Regional Military Command. Data analysis using SPSS and PLS.3.29 software with multivariate Structural Equation Model (SEM) analysis method. The results of this study indicate that: The influence of Strategic Leadership Style, Green Human Resource Management on Management Performance is positive and significant. The influence of Teamwork Management on Performance Management is positive and significant. The influence of Teamwork Management mediating Strategic Leadership Style, Green Human Resource Management on Management Performance is positive and significant. It means that the higher/positive mediation of Teamwork Management on Strategic Leadership Style, Green Human Resource Management, the higher/positive Management Performance. Improvement and development of quality and leadership style must first, pay attention to friendly and cooperative resources. Theoretical implications: Teamwork Management as mediating for Strategic Leadership Style, and Green Human Resource Management is able to improve Management Performance, by increasing Teamwork Management through increasing its dimensions will be able to improve Management Performance of the Jayakarta Military Regional Command (Kodam Jaya) Central Jakarta.